2019
DOI: 10.1016/j.ijhm.2019.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Examining the antecedents and consequences of trust in the context of peer-to-peer accommodation

Abstract: The theoretical understanding of peer to peer (P2P) accommodation has received much attention over the years; however, relatively little attention has been directed towards trust in peer to peer accommodation. Thus, the purpose of the present study is to develop and empirically test a model to understand the antecedents and consequences of guests trust toward peer to peer accommodation in the Egyptian context. Data collected from 793 respondents were analysed through partial least squares-structural equation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 119 publications
0
35
0
Order By: Relevance
“… Quantitative ( n = 148) Regression analysis (e.g., methods = binomial, binomial logistic, frontier, hedonic, instrumental variables probit, logistic, multinomial logistic, multiple, ordered logit, ordinal, ordinary least squares, panel, poisson, principal component, probability, quantile, spatial, stepwise, time series, tobit, weighted; software = R, SPSS, and Stata) 72 Abrate and Viglia, 2019 , Cai et al, 2019 , Falk et al, 2019 , Mahadevan, 2020 , Wu et al, 2017 , Xie and Mao, 2017 , Yang and Mao, 2020 . Structural equation modeling (e.g., method = covariance-based, partial least squares; software = AMOS, SmartPLS) 43 Agag and Eid, 2019 , Suess et al, 2020 . Other quantitative analyses (e.g., ANOVA, t -test) 33 Belarmino et al, 2019 , Guttentag et al, 2018 ; Experimental ( n = 14) Multiple experiment 8 Pera et al, 2019 , Shuqair et al, 2019 Quasi-experiment 3 Song et al, 2020 , Su and Mattila, 2019 .…”
Section: How Do We Know?mentioning
confidence: 99%
“… Quantitative ( n = 148) Regression analysis (e.g., methods = binomial, binomial logistic, frontier, hedonic, instrumental variables probit, logistic, multinomial logistic, multiple, ordered logit, ordinal, ordinary least squares, panel, poisson, principal component, probability, quantile, spatial, stepwise, time series, tobit, weighted; software = R, SPSS, and Stata) 72 Abrate and Viglia, 2019 , Cai et al, 2019 , Falk et al, 2019 , Mahadevan, 2020 , Wu et al, 2017 , Xie and Mao, 2017 , Yang and Mao, 2020 . Structural equation modeling (e.g., method = covariance-based, partial least squares; software = AMOS, SmartPLS) 43 Agag and Eid, 2019 , Suess et al, 2020 . Other quantitative analyses (e.g., ANOVA, t -test) 33 Belarmino et al, 2019 , Guttentag et al, 2018 ; Experimental ( n = 14) Multiple experiment 8 Pera et al, 2019 , Shuqair et al, 2019 Quasi-experiment 3 Song et al, 2020 , Su and Mattila, 2019 .…”
Section: How Do We Know?mentioning
confidence: 99%
“…Cheng and Jin [9] suggested that context, such as the general multiculturality and safety of an environment, can influence the attributes of short-term rental experiences. P2P accommodations entail a stranger-stranger transaction, which requires trust between the host and guest [15][16][17][18][19][20][21][22][23][24]. However, unlike in the Western market, interpersonal trust and safety are lower in The hospitality research includes a large body of literature investigating the attributes contributing to customers' satisfaction, quality of experience, hotel selection, and purchase intention [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found that photo, host description, self-uploaded information about providers and online review content have significant influences on user's trust towards providers on Airbnb [10,32]. Agag & Eid [33] confirmed that website quality, natural propensity to trust, and third-party recognition have positive effects on guests' trust towards hosts in the peer-to-peer accommodation context in Egypt.…”
Section: Antecedents Of Trust In the Sharing Economymentioning
confidence: 98%
“…Online trust-building mechanisms have been found to enhance consumer's trust towards sellers and platforms in the context of C2C and B2C e-commerce [13,18] and increase consumer's trust in the sharing economy [16,17,22,31,33]. These trust-building measures vary from company to company.…”
Section: Research Modelmentioning
confidence: 99%